Dinutuximab beta versus historical controls in the treatment of relapsed neuroblastoma: unadjusted and adjusted indirect comparisons - Lode, Holger N.; Holko, Przemysław; Wieczorek, Aleksandra; Śladowska, Katarzyna; Siebert, Nikolai; Valteau-Couanet, Dominique; Garaventa, Alberto; Cañete, Adela; Anderson, John; Yaniv, Isaac; Ash, Shifra; Moreno, Lucas; et al. (Frontiers in Oncology, 2026)
ObjectiveDinutuximab beta (dB) immunotherapy is used as maintenance treatment for relapsed/refractory neuroblastoma (NBL); however, comparative studies directly comparing dB with no dB therapy in this setting are lacking. This study aimed to indirectly compare dB (with or without interleukin-2) with no immunotherapy in patients with relapsed NBL.MethodsThree studies of dB (APN311-202, APN311-304, and APN311-303) with individual patient data, along with two historical control cohorts (INBR and R1) were included. Both unadjusted (naïve) and population-adjusted comparisons of overall survival (OS) were performed, with adjustment conducted using inverse probability or odds weighting. Harmonized inclusion criteria were applied across all study populations. The adjusted comparison used the propensity score reweighting to balance the cohorts based on key baseline prognostic factors.ResultsThe base-case unadjusted indirect comparison revealed that dB (with or without IL-2) significantly prolonged OS compared to historical controls not treated with dB (hazard ratio [HR], 0.43; 95% confidence interval [CI], 0.31– 0.79; p<0.001). Similarly, in the adjusted comparison, dB significantly prolonged OS compared to historical controls (HR, 0.53; 95% CI, 0.35; 0.79, p=0.002). All sensitivity unadjusted and adjusted comparisons supported the results of the base-case analysis.ConclusionDinutuximab beta significantly prolonged OS compared to historical control cohorts not treated with dB in both unadjusted and adjusted indirect comparisons.